Bates' guide to physical examination and history-taking. - Bickley, Lynn S.; Szilagyi, Peter G.; Bates, Barbara, 1928-2002. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2013)
"The 11th edition of the pre-eminent textbook on physical examination contains foundational content to guide students' approaches to history taking, interviewing, and other core assessment concepts, as well as fully illustrated, step-by-step techniques that outline correct performance of physical examination. The comprehensive, evidence-based content is intended for medical students, high-level nursing education and practice markets, as well as related health professions such as physician assistants. New for this edition: More than 200 new and revised photographs and drawings have been added to better illustrate key points in the accompanying text. Design and layout has been revised to increase discoverability of core material and special assessment tips. Techniques of interviewing chapter has been reorganized to provide clearer insights into the skills of empathic listening. Each chapter has been reviewed and revised to align with new evidence from sources such as Healthy People 2020, U.S. Preventive Services Task Force, Centers for Disease Control and Prevention, and American Cancer Society's Breast Cancer Facts and Figures. Highlights include: New information on guidelines for assessing obesity and nutrition, and managing acute and chronic pain. Extensive updates on the challenges of screening for cardiovascular disease, special populations at risk, steps for risk factor screening, and how to promote lifestyle and risk factor modification. New evidence-based guidelines on tobacco cessation, adult immunizations for influenza and pneumonia, hypertension screening, and risk-factor screening for dyslipidemia and metabolic syndrome. Updates on risk assessment for breast cancer, the Gail and Claus screening models, and BRCA1 and 2 mutations, as well as recommendations about mammography and clinical and self-breast examination. New screening guidelines for peripheral vascular disease, pap smears, prostate cancer, colon cancer, and risk factors for stroke and new information on sexually transmitted infections. Stronger focus on health promotion for children and adolescents. Expanded discussions of the functional assessment of older adults and minimizing risk of falls. New information on personality disorders and major mental health issues with significant emphasis on differentiating delirium, dementia, and depression"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Physical Examination -- methods; Medical History Taking -- methods